Terrestrial adult stages of freshwater insects are sensitive to insecticides. (January 2020) - Bruus, Marianne; Rasmussen, Jes Jessen; Strandberg, Morten; Strandberg, Beate; Sørensen, Peter Borgen; Larsen, Søren Erik; Kjær, Christian; Lorenz, Stefan; Wiberg-Larsen, Peter
Abstract: Terrestrial adult stages of freshwater insects may be exposed to pesticides by wind drift, over-spray, contact or feeding. However, studies addressing insecticide effects on freshwater invertebrates focus primarily on the impact of pesticides reaching the streams and potentially harming the aquatic juvenile stages. This is also reflected in the current risk assessment procedures, which do not include testing of adult freshwater insects. In order to assess the potential impact of insecticides on adult stages of freshwater insects, we exposed six common species to the insecticides Karate (lambda-cyhalothrin) and Confidor (imidacloprid). Dose-response relations were established, and LD50 estimates were compared to those of the honey bee, Apis mellifera L. (Hymenoptera: Apidae), which is the standard terrestrial test insect when pesticides are evaluated prior to commercial release. Generally, the tested species were more sensitive to the studied insecticides than the honey bee. In order to examine whether the sensitivity of adult stages of freshwater insects corresponds with the sensitivity of the juvenile stages of the same species, the ranking of the two life stages with respect to the toxicity of Karate was compared, revealing some correspondence, but also some dissimilarities. Our results strongly indicate that terrestrial adult stages of aquatic insects are not adequately protected by current risk assessment procedures. Highlights: Five of the six tested species were more sensitive to imidacloprid than the honeybee, when considering LD50 per individual. Three of the six species tested were more sensitive to imidacloprid than the honeybee, when LD50 per g dw was considered. All test species were more sensitive to lambda-cyhalothrin than the honey bee, irrespective of how LD50 was calculated. The ranking of juveniles and adults according to sensitivity to lambda-cyhalothrin was not identical.